2015
DOI: 10.1111/add.13211
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of education, social class and economic activity to the income–mortality association in alcohol‐related and other mortality in Finland in 1988–2012

Abstract: The income disparity in mortality among working-age Finns originates increasingly from alcohol-related causes of death. Roughly half the excess mortality in the lowest income quintile during 2007-12 is explained by the covariates of household income, education, social class and economic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…To reduce social inequality in health is recognized widely as an important policy issue [1][2][3], and alcohol has been found to contribute significantly to elevated rates of mortality and disability in lower social strata [4][5][6]. There is also evidence that the health consequences of adolescent drinking are considerable [7], and that a substantial proportion-approximately 20%-of all deaths among [15][16][17][18][19] year-olds in Europe is attributable to alcohol use [8].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce social inequality in health is recognized widely as an important policy issue [1][2][3], and alcohol has been found to contribute significantly to elevated rates of mortality and disability in lower social strata [4][5][6]. There is also evidence that the health consequences of adolescent drinking are considerable [7], and that a substantial proportion-approximately 20%-of all deaths among [15][16][17][18][19] year-olds in Europe is attributable to alcohol use [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tarkiainen et al considered that the income disparity linked to mortality statistics originated from alcohol-related deaths among the working aged population [52]. A Korean study reported that an increased alcohol-related mortality gap between social groups was attributable to increased alcohol consumption by socially disadvantaged middle-aged men after the economic crisis [53].…”
Section: Discussionmentioning
confidence: 99%
“…
Commentary on Tarkiainen et al (2016): Adding another piece to the puzzle of what explains socio-economic differences in alcohol-related mortality Despite literature on methods for reducing alcohol-related harm by socio-economic groups being scanty, high priority should be given to addressing the triad of low-income, nonemployment and substance abuse and to working towards smaller socio-economic disparities in alcohol-related harm.The importance of reducing the wide and, in many countries, still widening health disparities between socioeconomic groups is recognized widely [1], and in Finland [2] and many other European countries [3] alcohol use has been shown to play an important role in generating these inequalities. More research on the processes and mechanisms of these alcohol-related health disparities and on ways to reduce the differences has long been called for [4].

Tarkiainen et al

[5] add one piece to this puzzle.

…”
mentioning
confidence: 99%
“…Commentary on Tarkiainen et al (2016): Adding another piece to the puzzle of what explains socio-economic differences in alcohol-related mortality Despite literature on methods for reducing alcohol-related harm by socio-economic groups being scanty, high priority should be given to addressing the triad of low-income, nonemployment and substance abuse and to working towards smaller socio-economic disparities in alcohol-related harm.…”
mentioning
confidence: 99%
See 1 more Smart Citation